How Tourists Perceive, Create and Encode the Memorable Tourism Experience - Mendonça-Pedro, Rui; Mendes, Júlio; de Matos, Nelson; Passos Ascenção, Mário; Pinto, Patricia (Journal of Tourism, Sustainability and Well-being, 2021)
The focus of the study was to understand and clarify the role of the senses, emotions, and memories (SEMs) on the memorable tourism experience (MTE). The main objective of the research was to map the relation between the SEMs within the tourism experience establishment. The tourism experience mapping results showed that SEMs explained part of the MTE establishment and the discovery of three map patterns of the experience based on the emotional states of joy, love, and positive surprise. The research findings are relevant to reinforce the understanding, the design and to implement MTE more effectively, in terms of experiential stage planning and acting (service staff).